RESEARCHES OF THE COMBINATORIAL MODELS FOR INNOVATIVE INFORMATION TECHNOLOGIES - Riznyk, Volodymyr (International Journal of Computing, 2014)
The paper presents a new mathematical principle of innovative techniques for improving the quality indices of engineering devices and systems with non-uniform structure (e.g. coding systems) with respect to transmission speed, positioning precision, resolving ability, and functionality, using novel design based on remarkable properties and structural perfection of one- and multidimensional models of the systems, namely the concept of Ideal Ring Bundles (IRB)s prospected from basic laws of the world-wide harmony. Research into the underlying mathematical principle provides an ability to reproduce the maximum number of combinatorial varieties in the systems with a limited number of elements and bonds. This approach make it possible to configure systems with optimal placement of structural elements in spatially or temporally distributed systems, using the appropriate mathematical apparatus of contemporary combinatorial theory.